Osteoprotective effects of partially defatted house cricket (Acheta domesticus) powder in spontaneously hypertensive rats - Kukiat Tudpor; Kasama Wongprachum; Tarinee Nilkamheang; Chaloemporn Namyota; Nitchara Toontom; Le Ke Nghiep; Khuanjit Chaimongkolnukul; Surachai Chantip; Nontawan Choovattanapakorn; Panan Suntornsaratoon; Kannikar Wongdee; Jarinthorn Teerapornpuntakit; et al. (PLoS ONE, 2026)
Clinical evidence suggests that essential hypertension is linked to oxidative stress and inflammatory infiltration, which can complicate osteoporosis. Edible house crickets ( Acheta domesticus ) are novel functional foods rich in proteins, fat, dietary fibers, and micronutrients. This research investigated the effects of a partially defatted house cricket powder (PDCP) on bone microarchitecture and strength in the spontaneously hypertensive rat (SHR) model. Fourteen female SHRs were divided into the experimental group receiving 300 mg/kg/day PDCP and the control group receiving the vehicle for 4 weeks. Blood pressure was determined by the CODA ® non-invasive blood pressure system. Femoral bone microarchitecture and strength were determined by micro-computed tomography (µCT) and three-point bending, respectively. Immune cells were counted using an automated machine. Results showed that in the control group, systolic blood pressure (SBP) at baseline (166.6 ± 3.7 mmHg) increased to 182.4 ± 4.7 mmHg ( P = 0.016). In contrast, the PDCP-treated group showed no significant change from baseline (168.1 ± 3.9 mmHg) to post-intervention (176.9 ± 5.6 mmHg) ( P = 0.156). PDCP had no effects on bone microarchitecture but improved bone strength. The post-intervention yield load (a proxy for strength) of the control group was 77.55 ± 1.88 N, compared to the PDCP-treated group of 83.58 ± 1.26 N ( P < 0.009). Similarly, post-intervention yield displacement was 307.72 ± 29.78 in the control vs. 395.93 ± 40.98 µm in the PDCP-treated group. White blood cell counts in the PDCP-treated group (7.91 ± 0.27 × 10 3 /µL) were significantly higher than those in the control (6.91 ± 0.31 × 10 3 /µL). Specifically, lymphocyte counts in the PDCP-treated group (6.66 ± 0.22 × 10 3 /µL) were significantly higher than those in the control (5.75 ± 0.28 × 10 3 /µL). In conclusion, the 4-week PDCP had osteoprotective effects, presumably mediated by dietary proteins and fibers that modulate immune-vascular homeostasis, thereby potentially mitigating immune system-related hypertension and bone mechanical impairment.